Предмет: Алгебра,
автор: Nastjaaliska
25 баллов один пример, помогите!
Приложения:
![](https://files.topotvet.com/i/1e0/1e016e632b40b06e2f87ae369fb9b00e.jpg)
Ответы
Автор ответа:
0
x^2-3x+7=2x+1
x^2-3x+7-2x-1=0
x^2-5x+6=0
D=(-5)^2-4*1*6=1
x1=(5-1)/2=2
x2=(5+1)/2=3
Ответ: {2;3}
x^2-3x+7-2x-1=0
x^2-5x+6=0
D=(-5)^2-4*1*6=1
x1=(5-1)/2=2
x2=(5+1)/2=3
Ответ: {2;3}
Похожие вопросы
Предмет: Русский язык,
автор: raisartemiy
Предмет: История,
автор: KirillRRubtsov
Предмет: МХК,
автор: rusakovap69
Предмет: Биология,
автор: sawadewko
Предмет: Математика,
автор: vika12011